Reconstruction of the Criminal System in Corruption (Law Research Review Quarterly, 2019)
Corruption crimes is an iceberg phenomenon whose cases increase every year in Indonesia. The crime is carried out by person, groups of people, and corporations. Sadly, the perpetrators of corruption are also dragging the government or authorities, both executive, legislative, and judicial institutions. Policy by policy has been issued and there are even ad hoc institutions and special courts that handle these crimes. But in fact, this problem still not over, so there are indications that policies have not succeeded in overcoming corruption. The problems that have troubled the nation are very important to be studied scientifically. Reconstruction is needed for law enforcement efforts to deal with criminal acts of corruption, especially in its criminal system. This study aims to determine the criminal system of corruption and the reconstruction of the criminal system on corruption. This study uses a type of normative juridical research with the specification of the research is descriptive analytical. The data used is secondary data obtained through librarian and documentation studies which are then analyzed qualitatively. Based on the research, the results are: First, the criminal system on corruption acts refers to Law No. 39 of 1999 as amended by Law No. 20 of 2001 as its lex specialis. Second, the reconstruction of the criminal system can be directed at the rules of legislation governing material, formal, and implementing criminal law. In this case the researcher highlights criminal sanctions which include form, severity, and indicators of imposition of sanctions, and the methods of execution and coaching.